SUPPLY CHAIN MANAGEMENT AND INTEGRATION CONTROL - Sasanka S Mishra , Bibhuti B Pradhan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Supply Chain Integration (SCI) involves internal incorporation and external incorporation. External collaboration includes interaction with consumers and collaboration with vendors. The role of internal and external supply chain convergence and internal control has greatly impacted financial efficiency. The relevance of this analysis to supply chain management (SCM) is the incorporation of SCI and internal control variables to suggest a functional system for banks to use and the creation of a measurement device for managers to assess internal and external results. The goal of this paper is to use a newly established Supply Chain Integration System (SCI) to analyse the effect of a series of SCI and internal control ties. Supply chain management (SCM) is the administration of a network of integrated companies engaged in providing the commodity and service products needed by end users in a supply chain. Supply chain management involves the transportation and storing of raw resources, play-in-process stock, and finished items from point of production to point of use..